The Effect of Digital Snakes and Ladders of Human Excretion on The Motivation and Analytical Skills of High School Students - Zaqiyaturrohmaniah, Alfi; Alimah, Siti (Universitas Negeri Semarang, 2025)
The excretory system material is a material that has complex concepts and problems. This complexity requires interesting learning media facilities such as digital snakes and ladders game media. The aim of this research is to analyze the influence of digital snakes and ladders in human excretory system material on motivation and to analyze the influence of digital snakes and ladders in human excretory system material on students' analytical abilities. This research is a quantitative research with a one group pretest-posttest pre-experimental design. The sampling technique is purposive sampling. The population of this study were all class XI students of SMA N 1 Mlonggo. The sample used was 90 students. The instruments used are self-reflection sheets and tests. In this research, student learning motivation was analyzed descriptively quantitatively. Students' analytical abilities were analyzed using the Wilcoxon Signed Rank Test. The research results can be concluded that the average learning motivation after using digital snakes and ladders media is in the high category with a percentage of 79%. The result of students' analytical skills is that Ho is rejected where the probability or significance level is 0.000 (p value ≤ 0.05). This shows that the average pretest and posttest scores are significantly different. Based on these results, it shows that digital snakes and ladders in the human excretory system material have an effect on increasing students' motivation and analytical skills.